How FPGAs Can Help Create Self-Recoverable Antenna Arrays - Miroslav Joler (International Journal of Antennas and Propagation)
An approach to utilize Field Programmable Gate Array (FPGA) technology to control antenna arrays is presented based on the scenario of sensing a failure of any array element, analyzing degradation of the radiation pattern due to that failure, and finding a new set of excitations to the array elements in order to recover the radiation pattern as close to the original state as possible, thus creating a self-recoverable antenna array (SRA). The challenges of the SRA concept and embodiment of the recovery algorithm(s) are discussed. The results of the radiation recovery are presented on a few array cases, followed by a discussion on the advantages and possible limitations of the FPGA-based array control.